Dairy Slurry Application to Stubble-Covered Soil: A Study on Sustainable Alternatives to Minimize Gaseous Emissions - Silva, Arejacy António (2022)
The development of sustainable application practices, which do not demand incorporation into the soil, is necessary to encourage slurry use in conservation agriculture (CA). Incorporation is the most common practice to reduce nitrogen losses from the applied slurry. However, in CA, soil disturbance must be avoided. Two experiments were conducted to evaluate strategies to reduce gaseous emissions from dairy slurry applied to stubble-covered soil without incorporation. We evaluated (1) effects on ammonia (NH3) emissions of pretreatment by acidification (ADS), irrigation (IR) and placement under the stubble (US); and (2) effects of ADS, IR, US and delayed fertilization (RDS T16) on greenhouse gases (GHG). The results of the evaluated strategies were compared to raw slurry (RDS) and ammonium sulphate (MS). Additionally, in experiment 2, the results were compared to ammonium sulphate (MB) and slurry injection (IN), both in bare soil. ADS, US and IR decreased NH3 emissions by 66%, 60% and 32.5%, respectively, with total N emissions NH3 emissions accounting for more than 79% of N losses in slurry-based treatments. Late application reduced N2O emissions by 48%. GHG emissions from ADS, US and IR were similar to those from MS, MB and IN. ADS, US and IR are the most suitable strategies for slurry application in CA